Preparation of Rh5@Ptx/C core-shell nanoparticles for electrocatalytic oxidation of ethanol - Li Fang (2018)
© 2015 The Authors. Rh < inf > 5 < /inf > @Pt < inf > x < /inf > /C core-shell nanoparticles were prepared by a two-step hydrogen reduction process and characterized by cyclic voltammetry (CV) combined with X-ray diffraction (XRD) and transmission electron microscopy (TEM). The effects of the thickness of Pt shell on the catalytic performance for ethanol oxidation were investigated for activity performance evaluation. It was also found that Rh core was practically covered by Pt shell with a strong interaction between Rh and Pt although there was no PtRh alloy formation at the surface of the Pt shell during the deposition process for the catalyst preparation. The Rh core remarkably enhanced the catalytic activity of Pt shell and promoted the breaking of C-C bonds of ethanol resulting in relatively lower potential for the ethanol reaction. It can also be concluded that the current density of the oxidation peak on h < inf > 5 < /inf > @Pt < inf > 5 < /inf > /C was ca. 64 % higher than that on Pt < inf > 5 < /inf > /C although they both showed rather similar characteristic peaks.